Penerapan Bimbingan Kelompok “Kedamaian” Untuk Menurunkan Kecenderungan Perilaku Cyberbullying Pada Siswa SMP Negeri 17 Surabaya - Rahmawati, Feni Etika; Purwoko, Budi; Hariastuti, Retno Tri (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
Abstract: This study aims to examine the application of "Peace" Group Guidance to reduce the tendency of cyberbullying behavior in students of Junior High School 17 Surabaya. The results of this study can be an alternative in assisting counseling teachers to reduce the tendency of cyberbullying behavior by implementing "Peace" group guidance both preventively and curatively. The type of data used in this research is quantitative data. This research method used a quasi-experimental design with a non-equivalent control group design. Quantitative data were analyzed by normality test, homogeneity test and hypothesis testing.From the research results it is known that all variables have a significance value of > 5% or 0.05, which means that the data is normally distributed. And based on the homogeneity test it is known that the value of Sig. Based on the Mean is 0.668. Because the value of Sig. > 0.05, it can be concluded that the variance of the data is homogeneous. From the results of the hypothesis test, it can be seen that the value of Sig. (2-tailed) of the experimental group is 0.002 (p <0.05) and the value of t count is 5.024 > from t-table df 7 (2.36462). So that the results of the pre-test and post-test experienced significant changes (mean). And the test results can be seen the value of Sig. (2-tailed) of the control group is 0.465 (p> 0.05) and the value of t count is 0.773 < from t-table df 7 (2.36462). So that the results of the pre-test and post-test experienced insignificant (meaningful) changes. Based on the Independent Sample Test in the Equel Variances Assumed section, it is known that the value of Sig. (2-tailed) of 0.015 <0.05, then as a basis for making decisions on the independent sample t test it can be concluded that H0 is rejected and Ha is accepted. Which means there is a significant difference between the experimental and control groups. Or in other words, there is a significant difference in the tendency score of cyberbullying behavior before and after being given the application of Peace Group Guidance.Keywords: “Peace” Group Guidance, Tendencies in Cyberbullying BehaviorAbstrak: Penelitian ini bertujuan untuk menguji penerapan Bimbingan Kelompok “Kedamaian” untuk menurunkan kecenderungan perilaku cyberbullying  pada siswa SMP Negeri 17 Surabaya. Hasil penelitian ini dapat menjadi salah satu alternatif dalam membantu guru BK untuk menurunkan kecenderungan perilaku cyberbullying dengan menerapkan bimbingan kelompok “Kedamaian” baik secara preventif maupun kuratif. Jenis data yang digunakan dalam penelitian ini adalah data kuantitatif. Metode penelitian ini menggunakan metode quasi experimental design dengan desain non-equivalent control group design Data kuantitatif dianalisis dengan uji normalitas, uji homogenitas dan uji hipotesis.Dari hasil penelitian diketahui bahwa keseluruhan variabel memiliki nilai signifikansi > 5% atau 0.05 yang berarti bahwa data berdistribusi dengan normal. Dan berdasarkan uji homogenitas diketahui nilai Sig. Based on Mean adalah sebesar 0,668. Karena nilai Sig. > 0,05 maka dapat disimpulkan bahwa varians data adalah Homogen. Dari hasil uji hipotesis dapat dilihat nilai Sig. (2-tailed) dari kelompok eksperimen adalah 0.002 (p < 0.05) dan nilai t hitung 5,024 > dari t-tabel df 7 (2,36462).  Sehingga hasil pre-test dan post-test mengalami perubahan yang signifikan (berarti). Dan hasil uji dapat dilihat nilai Sig. (2-tailed) dari kelompok kontrol adalah 0,465 (p > 0.05) dan nilai t hitung 0,773 < dari t-tabel df 7 (2,36462).  Sehingga hasil pre-test dan post-test mengalami perubahan yang tidak signifikan (berarti). Berdasarkan Independent Sample Test pada bagian Equel Variences Assumed diketahui nilai Sig. (2-tailed) sebesar 0,015 < 0,05, maka sebagaimana dasar pengambilan keputusan uji independent sample t test dapat disimpulkan bahwa H0 ditolak dan Ha diterima. Yang berarti terdapat perbedaan yang signifikan antara kelompok eksperimen dan kontrol. Atau dengan kata lain terdapat perbedaan yang signifikan skor kecenderungan perilaku cyberbullying sebelum dan sesudah diberikan penerapan Bimbingan Kelompok Kedamaian.